Reproducibility between two readout methods of a commercial broth microdilution assay for Pseudomonas aeruginosa isolates from patients with Cystic Fibrosis. Issue 1 (2nd January 2019) - Franssens, Bas T.; Fluit, Ad C.; Rentenaar, Rob J.
Abstract: Background: Pseudomonas aeruginosa isolates from Cystic fibrosis (CF) patients are growing slowly, and frequently rendering automated susceptibility testing unsuitable. Colistin is an important antibiotic for treatment of P. aeruginosa infections. Broth microdilution is the only EUCAST endorsed antimicrobial susceptibility test for colistin. The VIZION™ device aids in reading broth microdilution plates and allows safe data transfer to laboratory information systems. In this study, reproducibility between visual MIC readout and readout, employing the VIZION™ device was assessed in susceptibility testing of colistin and beta-lactam antibiotics in P. aeruginosa isolates from CF patients. Methods: Fifty-six unique P. aeruginosa isolates were derived from respiratory secretions of CF patients. Susceptibility testing was performed using commercially available microdilution plates. MIC readout by VIZION™ was compared to visual readout aided by a mirror (reference test). Results: Pseudomonas aeruginosa isolates displayed significantly slower growth rates compared to quality control isolates. Colistin exact MIC agreement between VIZION™ and visual readout after 24 and 48 h incubation, respectively, was 82% and 95%, essential MIC agreement was 98% and 100%, categorical agreement was 98% and 98% and reliability (weighted kappa) was 0.95 (95% CI = 0.91–0.99) and 0.99 (95% CI = 0.97–1.00). For all five antibiotics, the total number of errors (using VIZION™, in comparison with visual readout) decreased from 15 (5%) to 10 (4%) after 24 and 48 h incubation, respectively. Conclusions: VIZION™ readout reproducibly determines MIC values in comparison with visual readout after 24 h of incubation. Reproducibility between the VIZION™ and visual readout increases after prolonged incubation of 48 h.